Impact of particle size on wheat dough and bread characteristics - Lapčíková, Barbora; Burešová, Iva; Lapčík, Lubomír; Dabash, Vikendra; Valenta, Tomáš (Food chemistry, 2019)
There was studied dough made from refined white and brown wheat flours of different granulometry by means of mechanical, thermal analysis and rheological testing. Observed results were confronted with textural properties of breads. Obtained data confirmed that fine refined white flour dough had high ability to elongate and accumulate stress, in contrary, brown fine flour dough exhibited weaker ability to accumulate stress. Observed increase of the complex viscosity associated with the gelatinization was the fastest in coarse dough, where it gained also the highest peak viscosity. The highest water content liberated was found from fine brown flour bread. This triggered lower water availability for hydration of starch granules in the bread during baking process, thus promoting higher moisture loss affecting thus the overall expansion and porosity of the bread matrix. The latter effect was ascribed to the presence of bran particles in brown flour.
Keywords: Triticum; velikost částic; Cooking; Flour; teplota; Particle Size; chléb; Uniaxial deformation; Rheology; Heating test; Crumb; Thermal analysis; Temperature; mouka; Texture; reologie; Granulation; viskozita; pšenice; Thermogravimetry; termogravimetrie; Viscosity; vaření; Bread; SEM